Experiences, Challenges, and Coping Strategies of Frontline Healthcare Providers in Response to the COVID-19 Pandemic in Kelantan, Malaysia - Che Yusof, Ruhana; Norhayati, Mohd Noor; Azman, Yacob Mohd (Frontiers in Medicine, 2022)
Introduction: In the fight against the COVID-19 pandemic, frontline healthcare providers who are engaged in the direct diagnosis, treatment, and care of patients face a high risk of infection and inadequate protection from contamination, overwork, frustration, and exhaustion. These impose significant psychological and mental health concerns for frontline healthcare providers. Objectives: This study aimed to explore the experiences and challenges faced and coping strategies adopted by frontline healthcare providers in response to the COVID-19 pandemic in Kelantan, Malaysia. Methodology: This phenomenological approach to qualitative study used a telephone-based in-depth interview that followed a semistructured interview guide. The number of frontline healthcare providers was based on saturation theory. All the participants recruited fulfilled the inclusion and exclusion criteria from May to July 2020 in Raja Perempuan Zainab II Hospital. All interviews were audio recorded and transcribed verbatim. Thematic data analysis using NVIVO version 10 was performed. Result: The ten respondents involved in this study consisted of doctors, medical assistants, and nurses. The findings were divided into four main themes: invaluable experiences during the pandemic, challenges, coping strategies, and future expectations. The providers responded well in facing the disease even though they felt psychologically disturbed at the initial phase of the COVID-19 pandemic. Conclusion: Healthcare providers perceived themselves as being more resilient and less vulnerable to psychological impacts than they were before the pandemic.